2019
DOI: 10.1371/journal.pone.0223607
|View full text |Cite
|
Sign up to set email alerts
|

Flexible learning spaces facilitate interaction, collaboration and behavioural engagement in secondary school

Abstract: Globally, many schools are replacing traditional classrooms with innovative flexible learning spaces to improve academic outcomes. Little is known about the effect on classroom behaviour. Students from nine secondary schools (n = 60, M age = 13.2±1.0y) were observed via momentary time sampling for a 30 minute period, in both a traditionally furnished and arranged classroom and a flexible learning space containing a variety of furniture options to accommodate different pedagogical approaches and learning styles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 35 publications
2
34
0
3
Order By: Relevance
“…In another study, 29 the 60 students observed cross‐sectionally spent significantly less class time being taught in a whole‐class setting, engaged in teacher‐led instruction and working individually in flexible learning spaces. Furthermore, students were observed spending significantly more time in group settings and collaborating in the flexible learning spaces than in traditional classrooms.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…In another study, 29 the 60 students observed cross‐sectionally spent significantly less class time being taught in a whole‐class setting, engaged in teacher‐led instruction and working individually in flexible learning spaces. Furthermore, students were observed spending significantly more time in group settings and collaborating in the flexible learning spaces than in traditional classrooms.…”
Section: Resultsmentioning
confidence: 94%
“…The 2 studies by Kariippanon et al, 29,30 were cross‐sectional with students spending a double period lesson (mean time = 80 minutes) in the flexible learning spaces. The remaining 3 studies by Byers 26,27 and Imms and Byers 28 were prospective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations